Green finance and renewable energy investments: A comparative analysis of successes, challenges, and policy implications across regions - Hadda Madouri (The Central European Review of Economics and Management (CEREM), 2025)
Aim: This study examines recent green finance developments to evaluate how institutional, economic, and policy factors affect renewable energy investments globally. It employs a comparative approach to identify key success drivers and barriers influencing the effectiveness of green finance in promoting renewable energy across different national contexts. Research Methods: The study systematically examines green finance impacts on renewable energy investments through a literature review, thematic analysis, and case studies. It reviews peer-reviewed articles (2015-2025). Prioritizing qualitative research, it analyzes policies, institutional frameworks, and outcomes. Comparing successful cases (e.g., Singapore, China) with failures (e.g., Middle East & Central Asia, Latin America) provides key insights. Findings: The findings depict a varied global scenario for green finance. Successes like Singapore's Green Bond Grant Scheme and China's Green Finance Pilot Zones showcase how strong regulations and blended financing boost renewable energy. In contrast, challenges in Africa (weak policies), Southeast Asia (high costs), and Latin America (political instability) emphasize the importance of tailored strategies to overcome structural obstacles. Originality: This study provides a unique comparative analysis of regional green finance initiatives, examining successes and failures. Unlike previous research, it identifies key factors and barriers, offering practical recommendations for policymakers. Addressing region-specific challenges enhances understanding of global green finance and supports sustainable development. Implications: The study underscores the necessity of strong regulations, blended finance, and regional collaboration for green finance success. Addressing weak governance, financing gaps, and political instability is crucial to scaling renewable energy investments and achieving sustainability goals globally. Limitations: Limited quantitative analysis; future research should explore hybrid financing models.
Keywords: G23; Q01; Q42; Q56; 330; Climate Finance; Green finance; renewable energy investments; sustainable development